2022
DOI: 10.3389/fncel.2022.864828
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 1 Function at Central Synapses in Health and Disease

Abstract: The transient receptor potential vanilloid 1 (TRPV1), a ligand-gated nonselective cation channel, is well known for mediating heat and pain sensation in the periphery. Increasing evidence suggests that TRPV1 is also expressed at various central synapses, where it plays a role in different types of activity-dependent synaptic changes. Although its precise localizations remain a matter of debate, TRPV1 has been shown to modulate both neurotransmitter release at presynaptic terminals and synaptic efficacy in post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 124 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…It is likely that these mediators, together with other factors, are involved in both the development and maintenance of mechanical pain. Since CBs and PPARs are localized also on glial cells [71][72][73], it is likely that at the level of non-neuronal cells, the changes in cytokine expression are directly mediated by endocannabinoids and related lipids, whose anti-inflammatory activity is already known [18,[74][75][76][77]. For instance, in neuropathic pain models, the activation of CB receptors reduced the expression of pro-inflammatory agents and increased the anti-inflammatory one [78] probably by the inactivation of transcription factors cAMP response element-binding protein (CREB) and nuclear factor kappa light chain enhancer of activated B cells (NF-κB) [79].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these mediators, together with other factors, are involved in both the development and maintenance of mechanical pain. Since CBs and PPARs are localized also on glial cells [71][72][73], it is likely that at the level of non-neuronal cells, the changes in cytokine expression are directly mediated by endocannabinoids and related lipids, whose anti-inflammatory activity is already known [18,[74][75][76][77]. For instance, in neuropathic pain models, the activation of CB receptors reduced the expression of pro-inflammatory agents and increased the anti-inflammatory one [78] probably by the inactivation of transcription factors cAMP response element-binding protein (CREB) and nuclear factor kappa light chain enhancer of activated B cells (NF-κB) [79].…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 is mainly present in trigeminal ganglion and dorsal root ganglion (Cha et al, 2020). In the CNS, TRPV1 is expressed in specific brain regions may involve in pain transmission and thermoregulation, such as thalamus, hypothalamus, cerebral cortex, cerebellum, striatum and substantia nigari (Meza et al, 2022). TRPV1 expression is augmented by neuronal injury and inflammation (Meza et al, 2022).…”
Section: Acetaminophen and Transient Receptor Potential Vanilloidmentioning
confidence: 99%
“…In the CNS, TRPV1 is expressed in specific brain regions may involve in pain transmission and thermoregulation, such as thalamus, hypothalamus, cerebral cortex, cerebellum, striatum and substantia nigari (Meza et al, 2022). TRPV1 expression is augmented by neuronal injury and inflammation (Meza et al, 2022). Notoriously, TRPV1 agonists inhibit inflammation by reducing the expression of pro-inflammatory TNF-α (Abdel- Salam et al, 2023).…”
Section: Acetaminophen and Transient Receptor Potential Vanilloidmentioning
confidence: 99%
“…A role in memory and learning in the CNS has also been proposed. Although there is no certainty about the precise location of TRPV1 at central synapses, it is known that the receptor can modulate both neurotransmitter release at presynaptic terminals, as well as the synaptic efficacy in postsynaptic compartments ( Matta et al, 2010 ; Meza et al, 2022 ). In fact, it has been observed that TRPV1 activity suppresses the excitatory transmission in the dentate gyrus of the hippocampus, and that its synaptic activation induces a form of long-term depression, mediated by endogenous anandamide ( Chávez et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%